A comparative study of the human resource practices prevalent in small and medium enterprises bumiputera and non-bumiputera in the Kuching/Samarahan district Sarawak - Siti Mariam, Abdullah (2000)
The objective of this research is to study four major human resource practices: recruitment and selection, training and development, performance appraisal and compensation, in small and medium enterprises in the district of Kuching/Samarahan, Sarawak and to compare the human resource practices of Bumputera and non-Bumiputera enterprises.Data was collected through the use of a questionnaire distributed to 500 respondents, consisting of 240 Bumiputera entrepreneurs and the rest non bumiputera entrepreneurs. Analysis of Varience (ANOVA) was used to analyse and identify the significant differences between Bumiputera and non-Bumiputera enterprises. The results obtained indicated that there are more human resource practices prevalent in Bumiputera than in non-Bumiputera enterprises, the most number being in the training and development function.